Cerebrospinal fluid circulation: evaluation by single-photon and positron emission tomography. - Bergstrand, G; Larsson, S; Bergström, M; Eriksson, L; Edner, G (American Journal of Neuroradiology, 1983)
Gamma camera cisternography after intrathecal administration of 111In-DTPA is a widely used and well established technique for studies of cerebrospinal fluid (CSF) circulation. The radiation dose from 111In, however, is a limiting factor that sometimes seriously affects the image quality and, hence, correct interpretation. This investigation was designed to assess the value of tomographic techniques for studies of CSF flow. Single-photon emission computed tomography (SPECT) was performed on 15 patients by means of the Karolinska Hospital rotating gamma camera system after injection of 111In-DTPA or 99mTc-DTPA. The combination of SPECT and 99mTc-DTPA proved to be a valuable technique. It permits a clear evaluation of the location of the isotope intracranially and its precise relation to the ventricles. Positron emission tomography (PET) applied after intrathecal administration of 68Ga-EDTA demonstrates that small amounts of radioactivity can be registered and that PET is a promising technique for the evaluation of CSF dynamics.